Blood leukocyte LINE-1 hypomethylation and oxidative stress in knee osteoarthritis - Nipaporn Teerawattanapong; Wanvisa Udomsinprasert; Srihatach Ngarmukos; Aree Tanavalee; Sittisak Honsawek (Heliyon, 2019)
Aim: Joints inflammation is one of the most pathologic processes leading to the development of osteoarthritis (OA), possibly leading to genomic instability. LINE-1 is transposable elements, and alterations in LINE-1 methylation induced by 8-hydroxy-2′-deoxyguanosine (8-OHdG) can cause genomic instability contributing to OA development. Herein, the present study examined associations between LINE-1 methylation, 8-OHdG, and knee OA severity. Methods: LINE-1 methylation levels were measured in 104 knee OA patients and 96 healthy controls by quantitative combined bisulfite restriction analysis. 8–OHdG was investigated by ELISA. The knee OA severity was appraised by questionnaires (VAS, WOMAC, KOOS, and lequesne index) and radiological severity based on the grading of Kellgren and Lawrence (KL) standard criteria. Key findings: Blood leukocyte LINE-1 methylation levels were significantly lower in knee OA patients than in healthy controls. Interestingly, individuals with LINE-1 hypomethylation were significantly associated with an elevated risk of knee OA. Linear regression analysis revealed that LINE-1 methylation was independently associated with KL grading of knee OA. Furthermore, plasma 8–OHdG levels in OA cases were not significantly different from those in healthy volunteers, whereas synovial fluid 8–OHdG values were considerably higher than in paired plasma specimens of the OA subjects. Significance: This study demonstrated that LINE-1 hypomethylation in blood leukocytes was associated with increased risk and radiographic severity of knee OA, and increased synovial fluid 8–OHdG levels were observed in knee OA patients. Collectively, LINE-1 hypomethylation and elevated 8–OHdG could emerge as biomarkers indicating the severity of knee OA and may take a possible part in the pathological process of knee OA.